A New Method to Measure the Job Satisfaction Level of an Employee - Islam, S. M. Shahidul (Engineering International, 2016)
Job satisfaction can simply be defined as the feelings people have about their jobs. As most people spend a major part of their adult life at work, job satisfaction is an important element of individual wellbeing. Employers always try to maintain high level job satisfactions of their employees to get best services of them, because job satisfaction inspires the workforce to work honestly and efficiently. There are many factors which play vital role in the job satisfaction of an employee. We summarize them by five factors namely payment, supervision, promotion opportunities, environment of the workplace and the work itself. Using these facets, we establish a new method to measure job satisfaction level of an employee in percentage. We illustrate our method with the help of an example.
Keywords: Job satisfaction; Satisfaction rank; Satisfaction ratio; Job satisfaction level